KONDISI EKOSISTEM TERUMBU KARANG DI PERAIRAN KRUENG RAYA, KABUPATEN ACEH BESAR - Nurul Najmi; M Rizki Fazillah; Muhammad Agustiar (JURNAL PERIKANAN TROPIS, 2021)
This study aims to analyze the condition of the coral reef ecosystem including the substrate, genus composition, and the level of coral mortality in the waters of the Malacca Strait, Masjid Raya District, Aceh Besar District. The research was conducted from October 2016 to October 2019 in the waters of the Malacca Strait, Masjid Raya District, Aceh Besar District. The research site is divided into three stations consisting of Lhok Mee Station, Ahmad Rhang Manyang and Benteng Inong Balee Station. Data were collected using the Point Intercept Transect method. The results showed that the condition of coral reefs at Lhok Mee Station was in the damaged category with coral cover ranging from 6.56% - 13.44%. Ahmad Rhang Manyang Station is included in the moderate to good category with coral cover ranging from 38.75% - 67.19%. Meanwhile, Benteng Inong Balee Station is included in the medium category with coral cover ranging from 45.94% - 56.88%. The monitoring results found that 30 coral genera with the highest composition of the coral genera came from the Porites genus, while other coral genera were unevenly distributed. The value of the mortality index for Lhok Mee Station shows a high increase in mortality of live coral to dead coral. Meanwhile, Ahmad Rhang Manyang and Benteng Inong Balee stations have low coral mortality index values.